Human Mesenchymal Stem Cells as a Carrier for a Cell-Mediated Drug Delivery - Litvinova, L. S.; Shupletsova, V. V.; Khaziakhmatova, O. G.; Daminova, A. G.; Kudryavtseva, V. L.; Yurova, K. A.; Malashchenko, V. V.; Todosenko, N. M.; Popova, V.; Litvinov, R. I.; Korotkova, E. I.; Sukhorukov, G. B.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
A number of preclinical and clinical studies have demonstrated the efficiency of mesenchymal stromal cells to serve as an excellent base for a cell-mediated drug delivery system. Cell-based targeted drug delivery has received much attention as a system to facilitate the incorporation and transfer of active substances to specific organs and tissues with high efficiency. Human mesenchymal stem cells (MSCs) are attracting increased interest as a promising tool for cell-based therapy due to their high proliferative capacity, multipotency, anti-inflammatory, and immunomodulatory properties. In particular, these cells are potentially suitable for use as encapsulated drug transporters to sites of inflammation. Here, we studied the in vitro effects of incorporating synthetic polymer microcapsules at various microcapsule to cell ratios on the morphology, ultrastructure, cytokine profile, and migration ability of human adipose-derived MSCs at various time points post phagocytosis. The data show that under appropriate conditions human MSCs can be efficiently loaded with synthesized microcapsules without damaging cell structural integrity with unexpressed cytokine secretion, retained motility and ability to migrate through 8 μm pores. Thus, the strategy of using human MSCs as a delivery vehicle for transferring microcapsules, containing bioactive material, across the tissue-blood or tumor-blood barriers to facilitate treatment of stroke, cancer or inflammatory diseases may open a new therapeutic perspective.